Human Compensation of Machine Translation Gaps - Aguilar-Amat, Anna (2021)
In the context of the transition from the information society to cyber-humanism, the human-machine relationship is explored from a user-centered psycho-translational perspective. Understanding the reasons for machine translation (MT) errors by expanding linguistic-cognitive awareness allows us to optimize message reception. Based on real examples of MT use, three types of users are distinguished and a novel nuance is formulated of the concept of 'compensation' (cognitive empathy) that completes Jakobson's communication scheme. Active and proactive cognitive-empathetic responses to MT errors are a key factor in multilingual communication.